Sweetpotato (Ipomoea batatas L.) - Mwanga, Robert O.M.; Andrade, M.I.; Carey, E.E.; Low, Jan W.; Yencho, George Craig; Grüneberg, W.J. (Springer, 2017)
Sweet potato has traditionally been viewed as a “poor person’s crop” or “orphan crop,” and it has attracted limited attention compared to other staple crops. However, during the last decade, this perception has changed, and it is widely acknowledged that sweet potato has great potential to contribute to the alleviation of malnutrition and hunger in the developing world. Orange-fleshed sweet potato, in particular, with its high provitamin A content, has become a prominent example of the effectiveness of biofortified staple crops to combat vitamin A deficiency. Similarly, increasing awareness of the nutritional value of sweet potato is driving consumer demand among health-conscious consumers globally, and its potential use in a wide range of value-added human and animal products is widely recognized. As the public and private sectors learn more about the benefits and opportunities of sweet potato, they have invested more in crop improvement; thus our understanding of the importance and potential of the crop is increasing. This chapter covers many aspects of sweet potato improvement with emphasis on the developing world. It includes sections on the history of sweet potato cultivation, general crop biology, the complex genetics and breeding challenges encountered by breeders seeking to improve the crop, crossing and breeding strategies for key traits, germplasm relations and the potential of wild relatives for crop improvement, and a section on seed production and the development of sustainable seed systems. It concludes with a review of advances in molecular genetics and genomics of the crop and the potential uses of these tools for sweet potato improvement.